2013
DOI: 10.1007/978-3-642-31659-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Perturbations in Alternative Pre-messenger RNA Splicing

Abstract: For most of our 25,000 genes, the removal of introns by pre-messenger RNA (pre-mRNA) splicing represents an essential step toward the production of functional messenger RNAs (mRNAs). Alternative splicing of a single pre-mRNA results in the production of different mRNAs. Although complex organisms use alternative splicing to expand protein function and phenotypic diversity, patterns of alternative splicing are often altered in cancer cells. Alternative splicing contributes to tumorigenesis by producing splice i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 316 publications
(168 reference statements)
1
39
0
Order By: Relevance
“…It has been reported that cancer cells show many alternative splicing events associated with progression, metastasis, and deregulation of splicing factors (Oltean and Bates 2013;Shkreta et al 2013). However, there have been few studies on splicing in the cancer-derived SH-SY5Y cells (Lannaccone et al 2013;Mikulak et al 2012;Saint Martin et al 2012).…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that cancer cells show many alternative splicing events associated with progression, metastasis, and deregulation of splicing factors (Oltean and Bates 2013;Shkreta et al 2013). However, there have been few studies on splicing in the cancer-derived SH-SY5Y cells (Lannaccone et al 2013;Mikulak et al 2012;Saint Martin et al 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Many cancer-related genes are regulated by AS, with the encoded proteins often involved in all major aspects of cancer cell biology. 31 The diversity and abundance of alternative UGT variants are suggestive of a physiological role, possibly in the control of coordinate cellular responses induced by small molecules and in determining exposure to xenobiotics. Given that several alternative variants are expressed at "biologically significant" levels (> 20 FPKM) 23 and some in the context of low canonical expression, alternative functions independent of UGT enzymes may be anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…A changed efficiency of splice site recognition is the immediate consequence, while irregularities in protein isoforms in different systems ultimately establish the disease state. Any of these alterations affecting alternative splicing can facilitate the appearance of characteristics in cancer cells, including the inappropriate proliferation, migration, methylation changes and resistance to apoptosis and chemotherapy (70). Alternative splicing has been implicated in nearly all aspects of cancer development, and therefore, is a main participant in the disease.…”
Section: Alternative Splicing and Diseasementioning
confidence: 99%